Light absorption by excited exciton states in layered InSe crystals - Zhirko, Yu.I.; Zharkov, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
We investigated spectra of light absorption by excitons in InSe crystals of different thicknesses, both pure and doped with iron group impurities, at temperatures from 4.5 up to 100 К. It was shown that, along with the traditional direct optical transition (photon → exciton → photon) at k = 0, exciton production and annihilation (accompanied with photon emission) occurs also via indirect vertical transition (photon ± phonon → exciton → photon ± phonon) at k ~ 0. For the n = 1 exciton state the direct and indirect vertical transitions were found to be compatible. For excited exciton states these transitions are not compatible; as a result, the integral intensity of absorption bands for excited exciton states, Kn, is over K⁰/n³ (where K⁰ is the classic value for the n = 1 exciton absorption band) and grows with temperature. For the n = 1 exciton state both symmetric and asymmetric (with phonon absorption only) indirect vertical transitions are considered.